Aktivitas Antibakteri Ekstrak Buah Asam Kalimbawan (Sarcotheca diversifolia (Miq) Hallier F) terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Indah Pratiwi; Rikhsan Kurniatuhadi; Rahmawati (Life Science, 2024)
Asam kalimbawan (Sarcotheca diversifolia (Miq) Hallier F) is a native plant found in Kalimantan, especially in West Kalimantan. This species belongs to the Oxalidaceae family, known for producing compounds with antioxidant and anti-inflammatory properties. This study aims to investigate the antibacterial activity of kalimbawan tamarind fruit extract against Staphylococcus aureus and Escherichia coli bacteria. Fruit extraction was carried out using the maceration method with methanol solvent, and the antibacterial activity was performed using the disc diffusion method. This research utilized a Completely Randomized Design (CRD) with seven treatment levels and four replications for each bacterium. The test concentrations of the extract against S. aureus and E. coli were 0.1, 0.2, 0.3, 0.4, and 0.5 g/mL, as well as ciprofloxacin and 10% DMSO. The study results revealed that all concentrations of the extract were able to inhibit the growth of the test bacteria, as indicated by the presence of a clear zone. The effective extract concentrations against S. aureus and E. coli bacteria were 0.4 g/mL and 0.3 g/mL, respectively, with corresponding zone diameters of 16.55 mm and 14.22 mm, respectively. Asam kalimbawan, which has been traditionally used by the people of Sambas Regency, has the potential to be developed as a source of natural metabolite-derived medicines.